Cloning and disruption of the UeArginase in Ustilago esculenta: evidence for a role of arginine in its dimorphic transition - Yafen Zhang; Min Wu; Qianwen Ge; Mengfei Yang; Wenqiang Xia; Haifeng Cui; Xiaoping Yu; Shangfa Zhang; Zihong Ye (BMC Microbiology, 2019)
Abstract Background Ustilago esculenta, a typical dimorphic fungus could infect Zizania latifolia and induce host stem swollen to form an edible vegetable called Jiaobai in China. The strains differentiation especially in the mating ability and pathogenicity is closely related to different phenotypes of Jiaobai formed in the fields. Dimorphic switching, a tightly regulated processes, is essential for the pathogenetic development of dimorphic fungi. In responses to environment cues, dimorphic switching can be activated through two conserved cell signaling pathways-PKA and MAPK pathways. Previous study indicated that exogenous arginine could induce hyphal formation in several dimorphic fungi through hydrolysis by arginase, but inhibit the dimorphic transition of U. esculenta. We conducted this study to reveal the function of arginine on dimorphic transition of U. esculenta. Results In this study, we found that arginine, but not its anabolites, could slow down the dimorphic transition of U. esculenta proportionally to the concentration of arginine. Besides, UeArginase, predicated coding arginase in U. esculenta was cloned and characterized. UeArginase mutants could actually increase the content of endogenous arginine, and slow down the dimorphic transition on either nutritious rich or poor medium. Either adding exogenous arginine or UeArginase deletion lead to down regulated expressions of UePkaC, UePrf1, mfa1.2, mfa2.1, pra1 and pra2, along with an increased content of arginine during mating process. Conclusion Results of this study indicated a direct role of arginine itself on the inhibition of dimorphic transition of U. esculenta, independent of its hydrolysis by UeArginase.